PENYULUHAN HUKUM MENGENAL DAN MEMAHAMI UNDANG-UNDANG NOMOR 1 TAHUN 2023 TENTANG KITAB UNDANG-UNDANG HUKUM PIDANA KEPADA MASYARAKAT KAMPUNG PALUH KECAMATAN MEMPURA KABUPATEN SIAK - Sukamariko Andrikasmi; Muhammad Haikal Muqsith; Ahmad Fahrudin; Abdurrahman Al Farisi; Natha Meliana (Jurnal Visi Pengabdian Kepada Masyarakat, 2023)
The outreach seeks to improve public accessibility by introducing and explaining the newly enacted Criminal Code and how to educate. Socialization is the obligation of all people who are aware of the law, including legal academics. The principle of legal fiction makes socialization urgent. Legally, the obligation to disseminate the new rules is regulated in Law Number 12 of 2011 concerning Formation of Legislation and Presidential Regulation Number 1 of 2007 concerning Ratification, Promulgation and Socialization. The purpose of this research is to find out the principles, types of crimes, qualifications of crimes and violations in the National Criminal Code and the status of specific crimes in the National Criminal Code. The method used in this Community Service activity is in the form of socialization and legal counseling. Good legislation meets the needs of society. New crimes require legal restrictions to suit the ever-changing period. From here, the Criminal Code Law No. 1 of 2023 was passed.